Preservation of residual hearing after cochlear implant surgery: an exploration of residual hearing function in a group of recipients at cochlear implant units - Gautschi-Mills,Katherine (2019)
Abstract Introduction: The preservation of residual hearing is becoming increasingly important in cochlear implant surgery. Conserving residual hearing is a positive prognostic indicator for improved hearing abilities. Objective: The primary aim of the study was to explore the preservation of residual hearing following cochlear implantation in a group of recipients at two major cochlear implant centers. Methods: A quantitative paradigm was adopted and exploratory research conducted within a retrospective data review design. The sample consisted of 50 surgical records and 53 audiological records from 60 observations (53 patients, seven of whom were implanted bilaterally). The records were selected using purposive sampling and consisted of records from participants ranging from six to 59 years of age. The average time of when the postoperative audiograms were performed in the current study was 24.7 months (s.d. = ±9.0). Data were analyzed through both qualitative and inferential statistics and a comparative analysis of unaided pre- and postoperative audiological test results was conducted. Results: Results indicated a high success rate of 92% preservation of residual hearing with half of the sample exhibiting complete preservation in cochlear implant recipients across all frequencies postoperatively. A total postoperative hearing loss was found in only 8% of cochlear implantees across all frequencies. There was no relationship between preoperative hearing thresholds and preservation of hearing postoperatively. The two main surgical techniques used in the current study were the contour on stylet and the advance off-stylet techniques, with the majority of surgeons utilizing a cochleostomy approach. From the findings, it became apparent that the majority of cases did not have any reported intraoperative complications. This is a positive prognostic indicator for the preservation of residual hearing. Conclusion: Findings suggest improved cochlear implant surgical outcomes when compared to previous studies implying progress in surgical techniques. The surgical skill and experience of the surgeon are evidenced by the minimal intraoperative complications and the high success rate of hearing preservation. This is a positive prognostic indicator for individuals with preoperative residual hearing as the preserved residual hearing allows for the potential of electro-acoustic stimulation, which in turn has its own hearing benefits.